2013
DOI: 10.1371/journal.pone.0057657
|View full text |Cite
|
Sign up to set email alerts
|

AaERF1 Positively Regulates the Resistance to Botrytis cinerea in Artemisia annua

Abstract: Plants are sessile organisms, and they can not move away under abiotic or biotic stresses. Thus plants have evolved a set of genes that response to adverse environment to modulate gene expression. In this study, we characterized and functionally studied an ERF transcription factor from Artemisia annua, AaERF1, which plays an important role in biotic stress responses. The AaERF1 promoter had been cloned and GUS staining results of AaERF1 promoter-GUS transgenic A. annua showed that AaERF1 is expressed ubiquitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…Moreover, two A. annua methyl jasmonate-responsive transcription factors, regulating expression of the first two artemisinin biosynthetic genes, were recently identified [39], as well as an A. thaliana MYC factor, involved in transcriptional control of two C15-TPS genes [40]. Further reports established a tight correlation between the A. annua ERF/AP2 transcription factor AaORA and the expression of three artemisinin pathway genes [41]. Understanding transcriptional regulation of terpenoid biosynthesis has considerable implications for pathway manipulation in cell or tissue cultures of medicinal plants.…”
Section: Engineering Through Transcriptional Controlmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, two A. annua methyl jasmonate-responsive transcription factors, regulating expression of the first two artemisinin biosynthetic genes, were recently identified [39], as well as an A. thaliana MYC factor, involved in transcriptional control of two C15-TPS genes [40]. Further reports established a tight correlation between the A. annua ERF/AP2 transcription factor AaORA and the expression of three artemisinin pathway genes [41]. Understanding transcriptional regulation of terpenoid biosynthesis has considerable implications for pathway manipulation in cell or tissue cultures of medicinal plants.…”
Section: Engineering Through Transcriptional Controlmentioning
confidence: 95%
“…To date, however, the results of transcription factor overexpression in periwinkle hairy roots or cell lines remain inconclusive [43,44]. Concurrently, enhanced expression of AaORA in A. annua resulted in an approximately 50% increase in artemisinin accumulation, and a 35% boost in DHAA (dihydroartemisinic acid) content, respectively [41]. This limited augmentation of product levels suggests involvement of additional factors.…”
Section: Engineering Through Transcriptional Controlmentioning
confidence: 99%
“…Few TFs have been reported from other plants that are involved in regulating terpene biosynthesis. They are Artemisia annua , AaWRKY1, AaERF1, AaERF2, AaORA1 and AabZIP1 (Lu et al ., ; Ma et al ., ; Yu et al ., ; Zhang et al ., ), cotton GaWRKY1 (Xu et al ., ), TaWRKY1 from Taxus chinensis (Wang et al ., ), rubber EREBP1 and HbWRKY1 (Chen et al ., ; Zhou et al ., ) and OsTGAP1 in rice (Miyamoto et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…Wounding is a common damage caused by biotic and abiotic stress, which could activate defense-related gene to prevent further damage. Some ERFs were also regulated by wounding, such as AaERF (Lu et al 2013) and LeERF1/2/ 4 (Tournier et al 2003). Our results showed that GbERFb was obviously up-regulated at 12 h post wounding.…”
Section: Discussionmentioning
confidence: 53%